Prognostic performance of optic nerve sheath diameters in CT images and serum procalcitonin levels in traumatic brain injury patients in the intensive care unit: A retrospective cohort study - Gürsoy, Canan; Gürsoy, Güven; Gümüş Demirbilek, Semra (Journal of Surgery and Medicine, 2019)
Aim: Traumatic brain injury (TBI) is one of the common emergencies with a high mortality rate. It is difficult to determine the mortality and prognosis of TBI in the intensive care unit (ICU). The aim of this study is to assess the prognostic relationship of optic nerve sheath diameters (ONSD) as seen on computerized tomography (CT) images as well as serum procalcitonin (PCT) levels to mortality and Glasgow Outcome Scale (GOS) scores of patients with traumatic brain injury in the ICU. Methods: Data from 78 traumatic brain injury patients who were admitted to an ICU, underwent brain CT and had serum PCT levels measured, were investigated retrospectively. Patients’ data were gathered from ICU medical records. The ONSD was measured at 3 mm behind the globe. Results: The mean age of the patients was 57.11 (17.07) years. 57.7% of the patients were males, and 42.3% were females. The cut-off ONSD and serum PCT values were evaluated to determine mortality and prognosis (Cut-off values: right ONSD: 5.44, left ONSD: 5.37, PCT: 3.95 for mortality; right ONSD: 5.26, left ONSD: 5.28, PCT: 2.29 for GOS, respectively). Conclusion: ONSD measurements and serum PCT levels are associated with mortality and prognosis in traumatic brain injury patients.